Cytochrome c assembly. Issue 3 (22nd January 2013) - Mavridou, Despoina A. I.; Ferguson, Stuart J.; Stevens, Julie M.
Abstract Cytochromes c are central proteins in energy transduction processes by virtue of their functions in electron transfer in respiration and photosynthesis. They have heme covalently attached to a characteristic CXXCH motif via protein‐catalyzed post‐translational modification reactions. Several systems with diverse constituent proteins have been identified in different organisms and are required to perform the heme attachment and associated functions. The necessary steps are translocation of the apocytochrome polypeptide to the site of heme attachment, transport and provision of heme to the appropriate compartment, reduction and chaperoning of the apocytochrome, and finally, formation of the thioether bonds between heme and two cysteines in the cytochrome. Here we summarize the established classical models for these processes and present recent progress in our understanding of the individual steps within the different cytochrome c biogenesis systems. © 2013 IUBMB Life, 65(3):209–216, 2013